Implementasi Metode Qiro’ati Dalam Pembelajaran Baca Tulis Al-Qur’an Santriwati Baru Di Pondok Pesantren Darul Muttaqien Bogor - Muthmainah, Liska; Suhendra, Suhendra; Hakiem, Hilman (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Qiroati is a method of reading and writing the Qur'an that was discovered by KH. Dachlan Salim Zarkasyi from Semarang in 1963. Darul Muttaqien Islamic Boarding School is one of the institutions in Indonesia that uses the qiroati method to improve and improve the reading and writing of the Al-Qur'an for its students. Because studying the science of recitation is fardhu kifayah, while reading the Qur'an using the science of recitation is fardhu 'ain. This study discusses the application of the qiroati method in improving students' reading and writing of the Qur'an. The background is the reasons underlying the Darul Muttaqien Islamic Boarding School to choose the qiroati method for students, knowing the implementation of learning to read and write the Qur'an with the qiroati method, as well as knowing the supporting and inhibiting factors at the Darul Muttaqien Islamic Boarding School. This research is focused on new female students, namely class 1 MTs students who have just entered the Islamic boarding school. The research used is descriptive qualitative research. The research subjects are caregivers, teachers, and students. In collecting the data using the method of observation, interviews, documentation and trigalius, by using data analysis, namely data reduction, data presentation, and verification. The results of this study indicate that the qiroati method in learning to read and write the Koran for new female students at the Darul Muttaqien Islamic Boarding School, where the new female students are class 1 MTs students who have just entered the Islamic boarding school, is running well. Keywords: Qiroati Method; Reading and writing the Qur'an